THE IMPORTANCE OF MODERN WORK ETIQUETTE - Xakimov A. A. (Web of Journals Publishing, 2024)
Any work has rules of communication — work etiquette. We tell you why you need it and what principles you need to follow in order to keep your job and good relationships with colleagues. Work etiquette is a set of rules on which employees communicate with each other, as well as with managers, clients and partners.
Keywords: Modern life, etiquette, work etiquette, principles, ethics, philosophical worldview, society.